2012
DOI: 10.1016/j.bone.2012.03.030
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age at menarche on cross-sectional geometry of bone in young adulthood

Abstract: Elucidating the somatic and maturational influences on the biomechanical properties of bone in children is crucial for a proper understanding of bone strength and quality in childhood and later life, and has significant potential for predicting adult fracture and osteoporosis risks. The ability of a long bone to resist bending and torsion is primarily a function of its cross-sectional geometric properties, and is negatively impacted by smaller external bone diameter. In pubescent girls, elevated levels of estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The basis for these differences is not fully understood, but understanding the differences is important because they are linked to cardiovascular and other health outcomes (Day et al 2015; Golub et al 2008; Joinson et al 2011; Lakshman et al 2009; Ritte et al 2013; Seselj et al 2012; Weir et al 1998; Widen et al 2012). Certainly sex steroids play a role in this sex specificity and so do sex chromosomes as is evidenced by the height in women with complete androgen insensitivity and Turner syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for these differences is not fully understood, but understanding the differences is important because they are linked to cardiovascular and other health outcomes (Day et al 2015; Golub et al 2008; Joinson et al 2011; Lakshman et al 2009; Ritte et al 2013; Seselj et al 2012; Weir et al 1998; Widen et al 2012). Certainly sex steroids play a role in this sex specificity and so do sex chromosomes as is evidenced by the height in women with complete androgen insensitivity and Turner syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Girls also experience puberty at younger ages than boys and are more likely to exhibit precocious puberty, while boys are more likely to have delayed puberty (Carel and Leger 2008; Palmert and Dunkel 2012; Styne and Grumbach 2012; Walvoord 2010). The factors that contribute to these differences are unknown but important because variations in the timing of puberty have been associated with higher risk for adult metabolic abnormalities, cancer and osteoporosis (Day, et al 2015; Golub, et al 2008; Joinson, et al 2011; Lakshman, et al 2009; Ritte, et al 2013; Seselj, et al 2012; Weir, et al 1998; Widen, et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…It may also be that the childhood SES measure we used does not adequately reflect the social stressors experienced by impoverished girls and young women. A third possibility is that childhood SES effects on femoral neck strength in women are masked by much larger changes in bone strength during the menarche [75] and the menopause transition [76]. …”
Section: Discussionmentioning
confidence: 99%
“…Because the timing of pubertal onset is inversely related with peak bone mass and may also affect bone geometric properties during young adulthood, (47,48) future research should aim to clarify whether interactions exist with regard to PA and the muscle-bone unit, especially in females where menarche-related increases in estrogen may alter patterns of mineralization following PA (ie, endosteal versus periosteal). Primarily, our use of cross-sectional data limit the inference of causality from our hypothesized path model.…”
Section: Discussionmentioning
confidence: 99%
“…Though our data are tightly controlled with regard to chronological age, we did not measure maturational status or history in our sample. Because the timing of pubertal onset is inversely related with peak bone mass and may also affect bone geometric properties during young adulthood, (47,48) future research should aim to clarify whether interactions exist with regard to PA and the muscle-bone unit, especially in females where menarche-related increases in estrogen may alter patterns of mineralization following PA (ie, endosteal versus periosteal). (18,49) Excess adiposity may also affect the muscle-bone unit in the context of adaptation to habitual PA. (50,51) Results of our sensitivity analyses suggested that further controlling for relative adiposity did not alter the outcomes of our models; however, participants in the current study were healthy and not obese.…”
Section: Discussionmentioning
confidence: 99%